2022
DOI: 10.1177/13623613211070865
|View full text |Cite
|
Sign up to set email alerts
|

The creator did not give me more than I can handle: Exploring coping in parents of Black autistic children

Abstract: There is a paucity of studies that center on the lived experiences of Black families raising autistic children, and major gaps remain in our understanding of how parents of Black autistic children cope with stressors. Drawing from the Black family stress and coping model, this mixed-methods study explored coping strategies utilized by parents of Black autistic children. Twenty-two parents completed the Ways of Coping Questionnaire and participated in semi-structured interviews. Using grounded theory methods, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…In one instance, for example, a parent reported resorting to legal assistance to obtain autism treatment services for their child. The disparities in diagnosis of children with autism are consistent with what has been reported in the literature [ 8 , 36 , 37 , 38 , 39 , 40 ]. Aylward et al reported that culturally and linguistically diverse and low-income children often do not receive autism-specific services during important developmental windows (e.g., ages 0–3 years) leading to racial, ethnic, and socioeconomic disparities in access to diagnosis, intervention, and other services for children with autism [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In one instance, for example, a parent reported resorting to legal assistance to obtain autism treatment services for their child. The disparities in diagnosis of children with autism are consistent with what has been reported in the literature [ 8 , 36 , 37 , 38 , 39 , 40 ]. Aylward et al reported that culturally and linguistically diverse and low-income children often do not receive autism-specific services during important developmental windows (e.g., ages 0–3 years) leading to racial, ethnic, and socioeconomic disparities in access to diagnosis, intervention, and other services for children with autism [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…Sociocultural factors reported in prior research on autism in other culturally and linguistically diverse populations [ 16 , 36 , 37 , 38 , 39 , 40 ] were reflected in the parents’ narratives from this study. These included parents’ concerns about possible stigmatization by their family members and the broader community related to the child’s autism, lack of awareness about developmental disabilities, and limited understanding of autism symptoms and treatment services [ 38 ].…”
Section: Discussionmentioning
confidence: 66%
“…Studies have found that some parents flourish in their caregiving role, such as engaging in positive social experiences in the autism community, gaining patience, and appreciating their children's success (Kim & Dababnah, 2020; Markoulakis et al, 2012). Additionally, while research has found that advocacy skills can help parents cope with stress (Ewles et al, 2014), another study found that Black parents of autistic children temper their advocacy efforts due to fears of appearing aggressive (Lewis et al, in press). In total, the literature suggests the need for multifaceted, culturally relevant intervention approaches which address both child and parent outcomes and acknowledge family strengths along with challenges.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Although the findings from these community-based studies were overall promising, we were limited in our ability to reach families awaiting clarification on their children's potential autism diagnosis. Given the evidence that Black children (regardless of family socioeconomic status 16 ) are at risk for diagnostic delays, 15,27 that Black families have unique stressors and strengths, 17,35 and that parents can experience distress while their children are waitlisted for developmental concerns, 26 the current study extended our previous research to Black children awaiting a developmental or autism evaluation. Specifically, we piloted a 12-session version of PTA for parents of Black children with suspected autism or other developmental delays and analyzed short-term changes in parent (stress and depression); family (needs/strengths, advocacy, learning support, social support, and community access); and child (social competence and problem behavior) outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…2 Research has found that Black parents of autistic children use a range of coping strategies, including optimism and reliance on social networks and faith communities, which require culturally responsive intervention approaches. 17 Although a handful of studies have specifically focused on the unique needs of Black Americans, 18 further research is needed to understand how to build on existing strengths and address barriers facing Black children and their families.…”
mentioning
confidence: 99%